Doença cerebelar em cães e gatos - Palumbo, Mariana Isa Poci; Romão, Felipe Gazza; Machado, Luiz Henrique de Araújo [UNESP]; Lourenço, Maria Lúcia Gomes; Sakate, Michiko (My University, 2010)
Diseases of the cerebellar system are common in small animals, and result in a clinical syndrome characterized by hypermetria, base-wide stance and intentional tremors of the head and body. All movements of the limbs are spastic and awkward. The neurological examination assists in the localization of lesions restricted to the cerebellum or in the detection of disorders relating to other parts of the nervous system, which characterizes a multifocal disease process. Neurological disorders in dogs and cats may suggest a very extensive list of differential diagnoses, since they may be caused by infectious, degenerative and traumatic processes, among others. The possible etiologies for cerebellar syndrome include: aplasia and hypoplasia, abiotrophy, cancer, vascular stroke and inflammatory disorders. The aim of this paper is to review the clinical signs that aid in the location of the cerebellar lesion and discuss the possible causes of this syndrome in dogs and cats.

Los trastornos del sistema cerebeloso son comunes en los pequeños animales, y dan lugar a un síndrome clínico caracterizado por hipermetría, aumento de la base de apoyo y temblores de la cabeza y del tronco. Todos los movimientos de las extremidades son espásticos e incoordinados. El examen neurológico ayuda en la localización de las lesiones en el cerebelo o en la detección de los trastornos relacionados con otras partes del sistema nervioso, caracterizando así una enfermedad multifocal. Los trastornos neurológicos en perros y gatos pueden tener origen en una gran cantidad de procesos infecciosos, degenerativos y traumáticos, entre otros. Las posibles causas para el síndrome cerebeloso son: aplasia o hipoplasia, abiotrofia, cáncer, derrames vasculares e inflamatórias. El objetivo de este trabajo es revisar los signos clínicos que ayuden en la localización de la lesión cerebelosa y discutir las posibles causas de este síndrome en perros y gatos.

As doenças do cerebelo são comuns em pequenos animais e resultam em uma síndrome clínica caracterizada por hipermetria, base ampla de sustentação e tremores intencionais de cabeça e tronco. Todos os movimentos dos membros são espásticos e desajeitados. O exame neurológico auxilia a localização de lesões cerebelares ou a detecção de disfunções relativas a outras porções do sistema nervoso, caracterizando um processo patológico multifocal. As afecções neurológicas de cães e gatos podem sugerir uma lista muito extensa de diagnósticos diferenciais, pois podem ser causadas por processos infecciosos, degenerativos e traumáticos, entre outros. As possíveis etiologias para a síndrome cerebelar incluem: aplasia, hipoplasia, abiotrofia, neoplasia, infarto vascular e distúrbios inflamatórios. O objetivo do presente trabalho é revisar os sinais clínicos que auxiliam na localização da lesão cerebelar e discorrer sobre as possíveis causas dessa síndrome em cães e gatos.
Cerebellar disease in dogs and cats
Enfermedad cerebelar en perros y gatos
Keywords: Veterinary neurology; Etiology; Neurological syndromes; Neurología veterinaria; Etiología; Síndromes neurológicos; Neurologia veterinária; Etiologia; Síndromes neurológicas